Schooling in the shadow of benevolence: The experience of scholarship recipients in affluent schools - Geyer, Kelly; Walton, Elizabeth (South African Journal of Higher Education, 2016)
In a quest for improved educational outcomes that will lead to access to and success in higher education and the workplace, many affluent independent South African high schools offer scholarship places to talented and deserving learners. Learners selected for ‘inclusion’ in these schools can be presumed to be given unquestioned benefits and yet the voices of these scholarship recipients are seldom heard. By listening to these learners in a study framed by the idea of ‘voice research’ we found that while grateful for this opportunity, they are also aware of the limits of benevolence and find that their full participation in the academic, sporting and social life of the school is constrained by their own disadvantaged economic positions. With reference to literature and the voices of the participants, we conclude that while offering many advantages, scholarship programmes have limitations which need to be acknowledged at an individual and systemic level.